A preliminary examination of social preference across assessors. (23rd December 2021) - Huntington, Rachelle; Schwartz, Ilene
Abstract: Three assessors conducted paired stimulus preference assessments with an adult with autism spectrum disorder, his mother, a staff member, and an unknown researcher. Results indicated that the participant preferred different social interactions with his mother, as compared to the other assessors. In a follow‐up reinforcer assessment, the social interactions identified as most preferred for each assessor produced higher frequency responding when compared to no consequence or nonmatching preference conditions. Results suggest that preference for social interactions may vary based on the assessor. Implications regarding the impact of the assessor in social preference assessments are discussed.